Pengembangan Media Belajar Berbasis Power Point Dalam Pembelajaran Bahasa Arab Materi Kosakata Siswa Kelas VII MTs - Nursafina, Santi; Najah, Zughrofiyatun (Al Maghazi : Arabic Language in Higher Education, 2025)
The learning process needs to be designed in an innovative and creative manner to create a conducive, interactive, and enjoyable learning environment. This study aims to develop a Power Point-based instructional media to support Arabic language learning for seventh-grade students at MTs Al-Khairiyah Sidomulyo. The main objectives of the research are to determine the feasibility of the media based on expert validation, assess student responses, and evaluate the effectiveness of the media on learning outcomes. This study employs a Research and Development (R&D) method using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The data collected are both quantitative and qualitative, analyzed using predetermined evaluation criteria to determine product feasibility. The results indicate that the developed Power Point-based media is considered feasible, with a material expert score of 64% and a media expert score of 88%. Student responses during field testing were categorized as good, with an average score of 77%. Furthermore, the use of this media was proven to improve students' learning outcomes compared to before its implementation. Therefore, this Power Point-based instructional media can serve as an effective alternative for enhancing the quality of Arabic language learning.